The implementation of green supply chain management: minimising environmental risk in the South African manganese and phosphate mining industry - Bvuma, Khomotso (My University, 2013)
This study explored the implementation of green supply chain with regard to minimizing environmental risk in the South African manganese and phosphate mining industries. A qualitative research paradigm methodology was used. Theoretical assumptions were utilized. References by other researchers in the green supply chain and mining supply chain were also used to broaden the knowledge horizons for the study. A total number of twelve supply chain and environmental professionals from the key role players in the South African manganese and phosphate mining industries were interviewed and provided valuable input to the study. The study determined lack of information sharing between the role players in the supply chain that lead to the discovery of themes and sub–themes. The study identified seven main themes and eleven sub-themes as challenges in the implementation of green supply chain. Recommendations to address the challenges areoutlined and include the introduction of cleaner production practices by using cleaner technologies, inclusion of environmental aspects in the sourcing strategy, among others. The achievement of all these will ensure sustainable development. Originating from the study are research recommendations for the South African manganese and phosphate mining industries. The recommendations include further research to establish a green supply chain model as well as perception and expectations of policy makers in the industries.
M. Tech. (Logistics, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Supply chain; Mining industry; Manganese mining; Phosphate mining; Green supply chain; South African mining industry; 658.50968; Physical distribution of goods -- Management; Green technology; Manganese mines and mining -- South Africa; Phosphate mines and mining -- South Africa; Business logistics